Comparison of Different Modes of Oral Health Education in Visually Impaired Children - Santhoshi Kayithi; Ansari Khaja R; Mekala Sirisha; Madala Manasa V; Onteru Pradeep (Wolters Kluwer Medknow Publications, 2024)
To compare the effectiveness of various modes of oral health education in visually impaired children. A total of 100 students aged 8-15 years were included. The children were divided randomly into four groups. Children in Group I received oral hygiene instructions through Braille pamphlets. In Group II, children received instructions through nonvisual desktop access (NVDA). For children in Group III, both Braille and NVDA were used to deliver the instructions. Children included in Group IV served as controls, who did not receive any information in any form for the study period. After oral examination to record plaque and OHI-S scores, a questionnaire was given to the children to assess their knowledge scores. The same questionnaire was repeated after 1 month to reassess the knowledge score in different groups. Chi-square test, Wilcoxon test, and post hoc analysis tests were used. The mean plaque scores among the control group children at the follow-up were significantly higher (2.5 ± 0.64) than any other group. Similarly, the control group had higher mean oral hygiene simplified scores (1.75 ± 1.32) than the Braille (1.12 ± 0.65), NVDA (0.85 ± 1.38), and Braille + NVDA (0.2 ± 0.64) groups at follow-up. With regards to the mean total knowledge score, the control group scored the least (2.16 ± 1.46), while the Braille, NVDA, and Braille + NVDA groups scored 3.16 ± 1.43, 4.52 ± 1.12, and 6.36 ± 0.52, respectively. Combination of Braille and NVDA was found to be effective in educating and motivating visually impaired children regarding maintenance of oral hygiene.